Correlation between the biomechanical characteristics and stability of the 143D movement during the balance phase in competitive Tai Chi - Huang, Ruifeng; Ma, Yong; Lin, Shijie; Zheng, Weitao; Liu, Lin; Jia, Mengyao (Frontiers in Bioengineering and Biotechnology, 2024)
Objective To explore the biomechanical factors affecting the stability of athletes in the 143D balance phase of competitive Tai Chi. Method The Vicon 3D motion capture system, Kistler 3D force platform, and Noraxon surface electromyography (sEMG) system were used to measure the joint angle, joint moment, center of gravity, ground reaction force, and sEMG data of athletes. The stability index was then calculated according to the formula. Pearson’s or Spearman’s correlation tests were used to analyze the associations between the biomechanical factors and stability index. Results (1) Medial lateral stability index (MLSI): A significant negative correlation was found between the ankle inversion angle of the supporting leg (SL) and MLSI (p < 0.05). (2) Anterior posterior stability index (APSI): Significant negative correlations were observed between the ankle intorsion angle, integrated electromyography (iEMG) of the gastrocnemius, and muscle contribution rates of the tibialis anterior, external oblique, and gastrocnemius of the non-supporting leg (NL) with the APSI (p < 0.05). The ankle dorsiflexion moment, iEMG of the rectus femoris and tibialis anterior, muscle contribution rate of the biceps femoris, and root mean-squared (RMS) amplitude of the gluteus maximus of the SL also showed significant negative correlations with the APSI (p < 0.05). Strong and significant negative correlations were also identified between the hip intorsion angle, iEMG of the tibialis anterior, and RMS amplitude of the rectus femoris of the NL with the APSI (p < 0.01). Further strong and significant negative correlation was also found between the RMS amplitude of the biceps femoris of the SL and APSI (p < 0.01). The knee extorsion angle of the NL was positively correlated with the APSI (p < 0.05). (3) Dynamic postural stability index (DPSI): The knee adduction angle, iEMG of the tibialis anterior, and RMS amplitude of the erector spinae of the NL were significantly positively correlated with the DPSI (p < 0.05). The knee abduction and hip extension moments of the SL were also significantly positively correlated with the DPSI (p < 0.05). Conclusion The ankle inversion angle of the SL impacts left–right stability, while the NL’s hip and ankle intorsion angles, knee extorsion angle, and exertion on the core muscle and SL’s main muscles, as well as exertion of specific muscles of the NL affect anterior–posterior stability. The hip extension and knee abduction moments of the SL, knee adduction angle, exertion on the tibialis anterior, and activation of the erector spinae of the NL significantly affect the overall stability of an athlete.